Bond Dissociation Enthalpy as a Tool to Study Urethane Degradation - Mallouhi, Julie; Viskolcz, Béla; Szőri-Dorogházi, Emma; Fiser, Béla (Hungarian materials and chemical sciences and engineering (Online), 2023)
Polyurethane is the most important class of polymers. It contains several urethane bonds, which connect the building blocks of the polymer. Thus, the chemical recycling and the degradation of the polymer depend on the strength of the urethane bond. To better understand polyurethane degradation at the molecular level, three model systems were created, carbamic acid, methyl N-methylcarbamate, and phenyl N-phenyl carbamate, and studied by using computational chemical tools. Each of the model compounds contained one urethane bond. Thus, the effect of various functional groups around this motif can be studied by comparing the corresponding bond dissociation enthalpies (BDEs) within these compounds. The BDEs were computed by using the B3LYP density functional theory (DFT) method in combination with the 6-31G(d) basis set in the gas phase. It was found that in the case of phenyl Nphenyl carbamate, the degradation is more probable because the corresponding BDEs are lower than in the other two compounds.